Risk factors for multiple recurrent ischemic strokes - Nevzat Uzuner; Gulnur Tekgol Uzuner (Brain Circulation, 2023)
BACKGROUND: Cardiovascular diseases, hypertension, diabetes mellitus, dyslipidemia, and atrial fibrillation are the most common modifiable risk factors for recurrent ischemic stroke. In this study, we aimed to find the risk factors associated with more than two recurrent ischemic strokes after the first-ever stroke. METHODS: We collected the ischemic stroke patients in our stroke registry data bank, and the eligible patients were followed for recurrent ischemic stroke after 2008. Our study consisted of 927 patients who were followed up for 9 years after the first-ever stroke. RESULTS: We found that 185 (20%) patients had a recurrent ischemic stroke, and another 32 (3.5%) patients had more than one recurrence after the first-ever ischemic stroke. The mean time for the first stroke recurrence was 1 year, and the mean time for the multiple stroke recurrences was 3 years. Significant risk factors for multiple recurrences were congestive heart disease (P < 0.015) and diabetes mellitus (P < 0.006). CONCLUSIONS: We concluded that even with the appropriate treatments, patients with congestive heart disease and diabetes mellitus have a higher rate of multiple recurrences for ischemic stroke after the first-ever ischemic stroke, indicating that more attention should be paid to this issue.